Return reasons to work after retirement: study with servers of a Brazilian University - Boehs, Samantha de Toledo Martins (2016)
This paper presents the analysis of return reasons to work of retired civil servers, through insertion in a acquirements dissemination program in a Brazilian University. They participated in the survey, quantitative and descriptive, 118 retired civil servers. It was identified that the return relates especially to the centrality of work, highlighting the reasons for feeling of usefulness, greater social interaction, desire to occupy idle time and personal realization.Keywords: Work; Retirement; Psychology.